Analysis of the relationship between learning styles and creativity with high school physics learning outcomes - Junita, Novia; Desnita, Desnita; Asrizal, Asrizal; Gusnedi, Gusnedi (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
Difficulties experienced by students in learning Physics include both students and teachers not being able to recognize their learning styles and students' lack of creativity in learning which will have an impact on learning outcomes. The aim of this research is to analyze whether there is a relationship between learning style and creativity with high school physics learning outcomes. This type of research is descriptive research with a correlational quantitative approach. The research population is State High Schools in Payakumbuh. Sample selection applies Purposive Cluster Sampling by selecting 1 from each school ranking, high, medium and low. The instruments used are the learning style questionnaire consisting of 26 items and the creativity questionnaire consisting of 27 items. The data analysis technique uses prerequisite analysis tests, namely the normality test; homogeneity test and hypothesis test using linearity test, multiple linear regression test and correlation test. The results obtained are as follows: (1) there is a positive relationship between learning style and learning outcomes. (2) there is a positive relationship between creativity and learning outcomes at a significance level of 5% or 0.05.